How do professional Australian Football League (AFL) players utilise social media during periods of injury? A mixed methods analysis. Issue 7 (July 2018) - Nankervis, Brodie; Ferguson, Laura; Gosling, Cameron; Storr, Michael; Ilic, Dragan; Young, Mark; Maloney, Stephen
Abstract: Objectives: The objective of this study was to explore how social media is used by a population of injured professional athletes, by comparing the content and frequency of posts on social media, pre and post-injury. Design: A retrospective mixed methods design was utilised. Methods: Professional Australian Football League (AFL) players, injured during the 2015 season, were included in the study. Publicly accessible social media profiles for these players were identified on Twitter and Instagram. All posts published on verified profiles, from four weeks prior to injury until return to play, were extracted. Thematic analysis was used to investigate the content of these posts, while univariate and multivariate linear regression was used to investigate the frequency of posts during this time period. Results: Two reoccurring themes were identified exclusively post-injury; 'supporting team from the sideline' and 'sharing information about injury and rehabilitation'. The frequency of total posts did not differ significantly pre and post-injury, but the frequency of injury related posts increased in the immediate post-injury phase, then decreased between 4–8 weeks and 8–12 weeks post-injury. The frequency of injury related posts was higher with more severe injuries. Conclusions: The findings of this study suggest that injured players use social media to seek social support from their followers, especially in the immediate post-injury period and after sustaining a severe injury. The role of social media in injury rehabilitation may warrant further investigation, to determine if it could be used to facilitate return to play.